Use of bond‐valence sums in modelling the diffuse scattering from PZN (PbZn1/3Nb2/3O3). Issue 6 (10th October 2014) - Whitfield, R. E.; Welberry, T. R.; Paściak, M.; Goossens, D. J.
<x xml:space="preserve">Abstract</x> This work extends previous efforts to model diffuse scattering from PZN (PbZn1/3Nb2/3O3). Earlier work [Welberry et al. (2005). J. Appl. Cryst.38, 639–647; Welberry et al. (2006). Phys. Rev. B, 74, 224108] is highly prescriptive, using Monte Carlo simulation with very artificial potentials to induce short‐range‐order structures which were deduced as necessary from inspection of the data. While this gives valid results for the nature of the local structure, it does not strongly relate these structures to underlying crystal chemistry. In that work, the idea of the bond‐valence sum was used as a guide to the expected behaviour of the atoms. This paper extends the use of the bond‐valence sum from a qualitative guide to becoming a key aspect of the potential experienced by the atoms, through the idea of the global instability index, whose square has been shown to be proportional to the density functional theory energy of some systems when close to the minimum energy configuration.